RANCANG BANGUN MEJA KALIBRASI 3 DOF DENGAN PENGATURAN SUDUT SEMI OTOMATIS BERBASIS ARDUINO SEBAGAI PENUNJANG PERANGKAT 3D SCANNER - Mochammad Sholeh; Muchammad Fadzilah; Ika Nur Karima (Politeknik Negeri Jakarta, 2017)
ABSTRACT3D scanner calibration process is the process of positioning the camera against the reference coordinates. Position the camera against this coordinate which will be used as a reference as a measurement of objects during the scanning process takes place. Calibration is done manually by adjusting the angle of rotation, the angle of the slope and the height of the calibration board in accordance with the position instructed in the software. Determination of rotation angle, slope angle and the height of the calibration board is considered less efficient because of the many movements performed.Seeing these problems then needed a tool of the calibration process in the form of a tilting swivel table that is able to adjust the angle of rotation, the angle of the slope and the distance of height with the control settings. Tilt turntable made 3 DOF, according to calibration requirement. The control system uses inputs in the form of a compass sensor for rotation, gyro sensor for slope and ultrasonic sensor for arduino mega archiino-controlled height with DC motor drive. The movement of a DC motor is adjusted to meet the needs of the angle of the calibration process and the need for scanning process angles. The change in turn angle can not be fulfilled due to failure to read data on the compass sensor. Change angle of inclination every 1º with tolerance ± 1 ° and change of height distance every 1cm with tolerance ± 1cm. A tilt rotating table top is made of a long rectangle each side that has a size of 40 [cm] and the size of the table is not bigger than 60 x 60 x 100 [cm] with a maximum load is 1 [kg]Keywords: 3D Scanner, Calibration, Tilting Rotary TableABSTRAKProses kalibrasi 3D scanner merupakan proses penentuan posisi kamera terhadap koordinat referensi. Posisi kamera terhadap koordinat ini yang nantinya akan dijadikan acuan sebagai pengukuran benda saat proses pemindaian berlangsung. Kalibrasi dilakukan secara manual dengan mengatur sudut putaran, sudut kemiringan serta jarak ketinggian papan kalibrasi sesuai dengan posisi yang diintruksikan pada software. Penentuan sudut putar, sudut kemiringan serta jarak ketinggian papan kalibrasi ini dinilai kurang efisien karena banyaknya gerakan yang dilakukan.Melihat permasalahan tersebut maka dibutuhkan alat bantu proses kalibrasi berupa meja putar kemiringan yang mampu mengatur sudut putaran, sudut kemiringan serta jarak ketinggian dengan pengaturan kontrol. Meja putar kemiringan dibuat 3 DOF, sesuai dengan kebutuhan proses kalibrasi. Sistem kontrolnya menggunakan input berupa sensor kompas untuk putaran, sensor gyro untuk kemiringan dan sensor ultrasonic untuk ketinggian yang diatur mikrokontroller arduino mega dengan penggerak motor DC. Pergerakan motor DC diatur agar memenuhi kebutuhan sudut proses kalibrasi serta kebutuhan sudut proses pemindaian. Perubahan sudut putar tidak dapat terpenuhi karena gagalnya pembacaan data pada sensor kompas. Perubahan sudut kemiringan dikendalikan setiap 1º dengan toleransi ± 1° dan perubahan jarak ketinggian dikendalikan setiap 1cm dengan toleransi ± 1cm.Kata Kunci: 3D Scanner, Kalibrasi, Meja putar kemiringan